Spatial variation of biochar production potential from surplus crop residues in India - Arindam Datta; Sutapa Dutta; Shivani Sharma; Md.Hafizur Rahman (Current Research in Environmental Sustainability, 2025)
India faces environmental issues due to large-scale seasonal in situ burning of crop residues, leading to air pollution and nutrient loss. Biochar application can increase soil carbon content, moisture, and nutrient content while reducing air pollution. India produces 156 Mt. of annual in situ surplus crop residues from ten major crops, with the highest potential for rice residue biomass in Sangrur, Punjab. Biochar could reduce greenhouse gas emissions by 405 Tg annually and its application to soil could sequester 7.5 Tg of carbon. However, competition between biochar and other crop residue management technologies requires a life cycle assessment for sustainable management.